If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = h(a + b) 0 = (a * h + b * h) 0 = (ah + bh) Solving 0 = ah + bh Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1ah' to each side of the equation. 0 + -1ah = ah + -1ah + bh Remove the zero: -1ah = ah + -1ah + bh Combine like terms: ah + -1ah = 0 -1ah = 0 + bh -1ah = bh Divide each side by '-1h'. a = -1b Simplifying a = -1b
| -7-6=x | | 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 | | 9x^2-42x+37=0 | | 11-3(x+4)+5= | | H-41=13 | | 24=3(x)-6 | | (10x+36y)+(2x+y)= | | 63=60.50p+17.50 | | 8x-4+8x-4+4+3=180 | | 9=3(x)-6 | | 152+8h= | | 19=b-3 | | -3=3(x)-6 | | -6.5z+7.5z= |